(untitled) (Journal of Universal Science Research, 2023)
This article deals with the semantics of phraseological units consisting mainly of antroponyms. It is known that antroponyms form the largest lexical-semantic group of onomastic units. Therefore, in this article, proper nouns have been analyzed in the English and Uzbek language from a linguacultural point of view using several examples.